Implementasi Algoritma Rete pada Aplikasi Rekomendasi Makanan Sehat - John Elmer Semaya; Seng Hansun (Ultimatics : Jurnal Teknik Informatika, 2014)
This study discusses about the features on healthy food, especially for people with chronic diseases such as patients with diabetes, obesity, hypertension, heart, liver cirrhosis, ulcers, tuberculosis, lung cancer, gout and kidney. The purpose of this research is to implement the Rete’s algorithm on healthy food recommendation application that everyone who has a less than ideal body weight and who suffers a chronic illness get food recommendations that can help the healing process. This study involves an expert, the specialist dietician who practices in hospitals. The result of this study is that users can get recommendations tailored healthy foodstuffs with his/her illness. Index Terms - recommended healthy food, recommendation system, Rete algorithm